Improving Project-Based Skills and Science Learning Outcomes of Learners through Project-Based Learning Model in Class VII-D SMP Negeri 1 Bojonegoro - Wijayanti, Cicik; Andari, Tri; Baity, Nur (Science Education and Application Journal, 2023)
This research was designed in accordance with Classroom Action Research (CAR). The purpose of this study was to improve the project-based skills and science learning outcomes of students through the Project-Based Learning (PjBL) model in class VII-D SMP Negeri 1 Bojonegoro in the 2022/2023 academic year, with a total of 32 students. This research was conducted in two cycles, each cycle consisting of four stages, namely planning, implementation, observation, and reflection. In this study, data collection was carried out using observation techniques and giving tests at the end of the implementation. The focus of observation in this class action research is project-based skills and student learning outcomes.The research instruments used to determine the level of success of learners are project-based skills observation instruments and cognitive or knowledge learning outcomes instruments. The indicators of success in this study are if 80% of students classically have project-based skills at least with the predicate B in each aspect of project-based skills assessment and if 80% of students classically get science learning outcomes above the Criteria for Achievement of Learning Objectives (CALO) which is 70. The results showed that there was an increase in the project-based skills of students classically, from cycle I of 2.43 or 60.75% with the predicate C to 3.4 or 86% with the predicate B in cycle II. There was also an increase in the completeness of students' learning outcomes classically, from cycle I of 78.10%, to 93.75% in cycle II. The conclusion of this study is that the application of the PjBL model can classically improve the project-based skills and science learning outcomes of students in class VII-D SMP Negeri 1 Bojonegoro in the 2022/2023 academic year.